KI HAJAR DEWANTARA’S LEADERSHIP TRILOGY OF THE MAIN CHARACTER OF LEAN ON ME MOVIE - Riswan Habsa; Hazairin Eko Prasetyo (Universitas Sarjanawiyata Tamansiswa, 2018)
The objective of this study was to describe (1) the types of Ki Hajar Dewantara’s Leadership Trilogy in Lean on Me movie, and (2) the influences of the main character’s leadership to the teachers and students in the movie. This study used qualitative research. Theobject of this study wasLean on Me movie’s transcript.There were 32 utterances analyzed in the movie to find all indicators of each component of the trilogy. Generally, the results of the researchshowed that the three principles of Ki Hajar Dewantara were expressed by Joe Clark as the main character in the movie; they wereing ngarso sung tulodo, ing madyo mangun karso, andtut wuri handayani. Based on the anaysis, the results showed; (1) the main character could be said as a good leader as he fulfilled all the three principles of Ki Hajar Dewantara’s Leadership Trilogy. There were 16 utterances in tut wuri handayani, 11 utterancesof ing ngarso sung tulodo, and 5 utterances ing madyo mangun karso that were shown from his attitudes, roles, and actions in being supportive, role model, and motivator to his teachers and students; (2) the main character, through the three principles of Ki Hajar Dewantara’s Leadership Trilogy influenced his teachers and the students.